Childish games and plays in Athens during the Classical Age - de Sousa, Luana Neres (Romanitas - Revista de Estudos Grecolatinos, 2020)
Acknowledging the importance of games and plays in the social interaction process and knowledge acquisition made by small children isn’t exclusive from contemporary society. Over the analysis of ancient greek texts, such as Plato’s Laws, it’s possible to observe that those activities receive important reflections about its relations with the educational process of the future Athenian citizen. Beyond text documentation, toys and infant plays are depicted in greek ceramic from the classical period, especially on choes, child’s exclusive use vases and related to the context of the Anthesteria. The objective of this article is to analyse the way games and plays are conceived by Plato on Laws, also, how they are represented over three choes examples from centuries V and IV B.C., objecting to understand in what measures those activities were related to the educational process of Athenian boys from this period.
Keywords: Games; Child plays; Education; Childhood; Ancient Greece